Finding the Return Path: Landmark Position Effects and the Influence of Perspective - Karimpur, Harun; Röser, Florian; Hamburger, Kai; Justus Liebig University Giessen (My University, 2016)
Much research has been done on how people find their way from one place to another. Compared to that, there is less research available on how people find back from the destination to their origin. We first present theoretical approaches to perceptual and cognitive processes involved in finding a return path, including concepts such as visibility, structural salience and allocentric versus egocentric perspective, followed by a series of three experiments. In these experiments, we presented subjects intersections that contained landmark information on different positions. In order to investigate the processes involved, we used different measures such as route-continuation (in learning direction and in opposite direction) and free-recall of route information. In summary, the results demonstrate the importance of landmark positions at intersections (structural salience in combination with perspective) and that finding the return path is more difficult than reproducing the same route from the learning condition. All findings will be discussed with respect to the current research literature on landmark-based wayfinding.
Keywords: wayfinding; navigation; spatial cognition; return path; landmarks; ddc:150